Evaluasi Penerapan Muatan Pembelajaran PJOK dalam Kurikulum 2013 Pasca Pelatihan Guru Sasaran Sekolah Dasar Di Kota Kediri - Wita Suwarna (Jurnal Simki Postgraduate, 2023)
The curriculum is a set of plans and arrangements regarding objectives, content and learning materials, as well as the methods used as guidelines for organizing activities to achieve certain educational goals. Curriculum in Evaluation is a process of giving/determining values or appreciation of data obtained from periodic measurement results, and the type of research is evaluation research, the model used is the CIPP model. The type of research is evaluation research, the model used is the CIPP model, there are 12 elementary schools studied in the city of Kediri, focusing on teaching physical education and health teachers in elementary schools, the instrument used in the CIPP model evaluation research is a questionnaire developed by researchers who has gone through the expert validation stage. Research data analysis techniques using quantitative descriptive. The research process begins with the development of an instrument in the form of a questionnaire that has been validated by experts. After the questionnaire is ready to be used, data collection is carried out to obtain results for the Context component with an average value of 3.25. while for the input component the average value is 3.11., while for the Process with an average value of 3.18., while for the Product component the average value is 3.24. The conclusions from the research results are (1) Physical and health education teachers in primary schools are able to plan the 2013 curriculum based on the suitability between concepts and post-training learning in the field, with evaluation results showing that context is in the sufficient category, input is in the sufficient category, Process is in the sufficient category while the Product is in the sufficient category. (2). Physical and health education teachers are able to apply learning according to the PJOK curriculum RPP after the K.13 training in target elementary schools in Kediri City, with evidence that the CIPP results as a whole are in the sufficient category.